The Role of Social and Emotional Learning in Student Success - Zilva, De Razeek (Journal of Education Review Provision, 2023)
It is the intention of this paper to look at the impact of SEL on student achievement. This research work adopt a quantitative research method with an experimental design to test the presence of SEL competencies and students’ academic performance as measured via Pearson correlation coefficient test. Data were collected from 200 high school students in Jakarta through a survey that assessed five key SEL competencies: these include the aspects of self- awareness, self- regulation, social awareness, interpersonal skills as well as responsible choices. It was noted that all competencies of SEL had positive correlation with student achievement with self-management having the highest correlation coefficient. In the multiple linear regression analysis the five SEL Competencies accounted for 55% of the variance in academic performance. These results corroborate the need for implementing SEL programmes in educational settings earlier in students’ learning so as to enhance their academic performance as well as their emotional and social development.